2021
DOI: 10.1002/ijgo.13565
|View full text |Cite
|
Sign up to set email alerts
|

Giving birth during the COVID‐19 pandemic: The impact on birth satisfaction and postpartum depression

Abstract: Women who gave birth during the pandemic shown higher dissatisfaction with childbirth and more postpartum depression symptoms than those who gave birth before the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 24 publications
3
65
2
Order By: Relevance
“…Total scores range between 0 and 40, with higher scores indicating more perceived stress. In the present study, perceived stress was classified as low (0-13), moderate (14-26), or high (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as suggested by others [35,36]. The PSS-10 scale had good reliability (Cronbach's alpha = 0.89).…”
Section: Primary Outcomes and Psychological Questionnairessupporting
confidence: 49%
“…Total scores range between 0 and 40, with higher scores indicating more perceived stress. In the present study, perceived stress was classified as low (0-13), moderate (14-26), or high (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as suggested by others [35,36]. The PSS-10 scale had good reliability (Cronbach's alpha = 0.89).…”
Section: Primary Outcomes and Psychological Questionnairessupporting
confidence: 49%
“…Recent reports have documented the psychological impact of the COVID-19 pandemic among pregnant and postpartum women, including increased incidence of depression and anxiety (Ceulemans et al, 2020;Durankuş & Aksu, 2020;Parra-Saavedra et al, 2020;Zanardo et al, 2020). Additionally, a report from Spain observed associations between giving birth during the pandemic with poorer birth experience and postpartum depression (Mariño-Narvaez et al, 2020). Our findings add to this literature by demonstrating a n of some covariates do no not total 237 due to missing data b Chi-Square test c SARS-CoV-2 status defined from PCR test results (if available) using medical record data, or self-reported results (if no record); percentages are of the total women tested d Based on medical record data…”
Section: Discussionmentioning
confidence: 99%
“…Marino-Narvaez et al in their research found that women who gave birth during the COVID-19 pandemic in Spain reported lower quality of care if compared with women who gave birth before the pandemic (Marino-Narvaez et al, 2020). However, our research shows that despite the elevated proportion of women who had to give birth without the participation of a support person, the overall birth experience and provided care was not significantly inferior for women giving birth during the COVID-19 pandemic if compared with the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Since the outbreak of COVID-19, research has been done to assess the effects on maternal mental health. Elevated depression, anxiety and post-traumatic stress disorder symptoms have been reported among women who gave birth during the COVID-19 pandemic (Wu et al, 2020;Ostacoli et al, 2020;Marino-Narvaez, Puertas-Gonzalez, Romero-Gonzalez, & Peralta-Ramirez, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation